Banking governance, performance and risk-taking conventional banks vs Islamic banks - Ben Bouheni, Faten; Ammi, Chantal; Levy, Aldo (Innovation, entrepreneurship and management series, 2016)
This book explains the features of both conventional and Islamic banking within the current international context. It also provides a comparative view of banking governance, performance and risk-taking of both finance systems.